Performance of decode-and-forward over Nakagami-m fading channel in cooperative wireless networks. (November 2016) - Hikmat, Qabas Ali; Dai, Bin; Khaji, Rokan; Huang, Benxiong
Abstract: In this paper, we analyse the performance of a decode-and-forward (DF) multi-relay system over Nakagami- m fading channels. First, the closed form expression for the symbol error rate (SER) for both M phase shift keying (MPSK) and M quadrature amplitude modulation (MQAM) signals is derived using the concept of moment generating function (MGF) in the high signal to noise ratio (SNR) and determining a tight SER lower bound that converges to the same limit as the theoretical upper bound. Next, by optimising SER, we can identify the optimal amount of power that should be allocated at the source and relay nodes to develop an optimal power allocation (OPA) technique to reduce the SER. The validation of the theoretical analysis is corroborated by the simulation results of the proposed model over Nakagami- m fading compared to the various schemes regarding the performance in terms of the model's achievable SER and OPA.